SELECTION OF YOUNG HANDBALL PLAYERS METHODS AND METHODS (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In this article, I thought about the methods and techniques for selecting young handball players and explained the methods and techniques that can be applied in practice, based on the experience of teachers and coaches. I also shared my findings with recommendations on how to choose handball players and how to train with them.